In Vitro Antioxidant Activity and Phytochemical Screening of Aquilaria Malaccensis Leaf Extracts - Nik Noor Asma, Nik Wil; Nor Adila, Mhd Omar; Noorhuda, Awang@Ibrahim; Saiful Nizam, Tajuddin (JOCPR, 2014)
The present study investigated water extraction (WE) and methanol extraction (ME) of A. malaccensis dried leaves (DL) and fresh leaves (FL) for its in vitro antioxidant activity that may contribute to their pharmacological effects. Total phenolic content (TPC) of this plant was determined by Folin-Ciaocalteu assay, while antioxidant potential were evaluated by TAC, CUPRAC and DPPH method. Tests for steroids, triterpenoids, flavonoids, saponins, tannins and alkaloids were positive in both water and methanol extracts. WEDL showed the highest inhibition of the DPPH radical (48.07 ± 0.68 %) at concentration 1000 ug/ml and IC50 value was found to be 1.091 mg/ml, relative to ascorbic acid, having an IC50 of 0.219 mg/ml. It also showed the highest CUPRAC value (3.32 ± 0.01µg/ml) as well as the highest TPC and TAC (181.11 ± 0.61 and 398.74 ± 0.66 gallic acid equivalent (GAE) mg/g) at a concentration of 1000 µg/ml) as compared to the other studied extracts. In conclusion, the results of this study clearly indicated that the extracts of A. malaccensis possess significant antioxidant activities and could be used as a potential source of natural antioxidant agents that may be due to the presence of phytochemicals.